Calibration of Reflectivity Observations from the Weather Radar Network of Cyprus Against GPM Dual-Frequency Precipitation Radar - Loulli, Eleni; Bühl, Johannes; Michaelides, Silas; Loukas, Athanasios; HADJIMITSIS, DIOFANTOS (My University, 2024)
This paper analyses polarimetric weather radar data to explore their potential for comprehensive and reliable precipitation and thus, drought monitoring in Cyprus. Reflectivity measurements from the two ground-based X band dual-polarization radars of the Department of Meteorology of the Republic of Cyprus are compared with measurements obtained from the Dual-Frequency Precipitation Radar (DPR) onboard NASA’s Global Precipitation Measurement (GPM) mission in order to calibrate the ground-based reflectivity. The comparison is done using a volume matching method that allows us to associate the datasets both in space and time. To correct the attenuation, we examine a Z-A relationship approach and the forward gate-by-gate attenuation correction based on an iterative approach with scalable constraints. Preliminary results show a significant underestimation of the ground based reflectivity, as well as a notable impact of attenuation that leads to a major source of error for rainfall estimation
Keywords: X-band polarimetric weather radar; GPM DPR Ku-band; volume matching; attenuation correction